2020
DOI: 10.1093/database/baaa069
|View full text |Cite
|
Sign up to set email alerts
|

WCSdb: a database of wild Coffea species

Abstract: Coffee is a beverage enjoyed by millions of people worldwide and an important commodity for millions of people. Beside the two cultivated species (Coffea arabica and Coffea canephora), the 139 wild coffee species/taxa belonging to the Coffea genus are largely unknown to coffee scientists and breeders although these species may be crucial for future coffee crop development to face climate changes. Here we present the Wild Coffee Species database (WCSdb) hosted by Pl@ntNet platform (http://publish.plantnet-proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The Coffea genus currently comprises 130 recognized species, but this number rises up to 141 when all the taxa are included [ 10 ], most of which are cross-pollinated and distributed in Africa, Madagascar, the Comoros, the Mascarene Islands and Australasia [ 11 , 12 ]. Some of these such as C .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Coffea genus currently comprises 130 recognized species, but this number rises up to 141 when all the taxa are included [ 10 ], most of which are cross-pollinated and distributed in Africa, Madagascar, the Comoros, the Mascarene Islands and Australasia [ 11 , 12 ]. Some of these such as C .…”
Section: Introductionmentioning
confidence: 99%
“…The Coffea genus currently comprises 130 recognized species, but this number rises up to 141 when all the taxa are included [10], most of which are cross-pollinated and distributed in Africa, Madagascar, the Comoros, the Mascarene Islands and Australasia [11,12]. Some of these such as C. liberica, C. dewevrei, C. stenophylla [13], C. mauritiana, C. congensis, C. racemosa, C. zanguebariae, C. bengalensis, C. travancorensis, C. wightiana [14], C. eugenioides and C. humblotiana are or were consumed in the past, then abandoned for various reasons [15].…”
Section: Introductionmentioning
confidence: 99%
“…Among 139 coffee species so far identified [1] Coffea arabica L. (Arabica coffee) and Coffea canephora Pierre ex A. (Robusta coffee) are the only two species commercially cultivated around the world [2].…”
Section: Introductionmentioning
confidence: 99%
“…15 The Coffea Biological Resources Center (BRC Coffea), maintained on Reunion Island, is the result of numerous prospecting and campaigns in Africa (Cameroon, Ivory Coast, Ethiopia, Guinea, Kenya, Central African Republic (CAR), Republic of Congo, Tanzania), with the participation or support of national agronomy research centres and international institutions over a period from the 1960s to the 1980s. To date, the BRC Coffea collection houses 35 Coffea species 16 (http:// florilege.arcad-project.org/fr/crb/coffea). Thanks to the availability of genetic resources at BRC Coffea, which includes species sourced in Cameroon, we were able to conduct the study reported here.…”
Section: Introductionmentioning
confidence: 99%
“…From left to right: C. brevipes (A,B), C. congensis (C,D) and C. stenophylla (E,F). Individual pictures were extracted from the Wild Coffea species database 16 (Picture ©E Couturon IRD, under Licence Creative Commons, https://doi.org/10.23708/JZA8I2).…”
Section: Introductionmentioning
confidence: 99%